CLINICAL UTILITY OF RETICULOCYTE INDICES IN THE DIAGNOSIS AND MANAGEMENT OF PAEDIATRIC SICKLE CELL DISEASE PATIENTS IN PORT HARCOURT, NIGERIA - Jeremiah, Zaccheaus; Odozi, Choice; Jeremiah, Bliss; Okechukwu, Chioma (Sanamed, 2025)
Introduction:Sickle cell anemia (SCA) is a hereditary blood disorder resulting from a point mutation in the β-globin gene, leading to the production of abnormal hemoglobin S that distorts red blood cell morphology and impairs their function. Reticulocyte indices, which measure immature red blood cells in circulation, are key indicators of bone marrow response and erythropoietic activity in SCA patients. Materials and Methods: This cross-sectional study examined reticulocyte indices in individuals with sickle cell anemia. It involved 45 children aged 2 to 19 at the Rivers State University Teaching Hospital. Blood samples were collected from each patient and placed in EDTA bottles. Reticulocyte counts were performed using the New Methylene Blue staining method and counted under a light microscope. Hemoglobin (Hb) and packed cell volume (PCV) were measured with a Veri-Q RED Hemoglobin meter. Reticulocyte indices, including absolute reticulocyte count (ARC), reticulocyte index (RI), and reticulocyte production index (RPI), were calculated using MDCalc.Results: The mean reticulocyte count was 1.33 ± 0.22%, while the mean reticulocyte production index was 0.40 ± 0.09. Reticulocyte production index (RPI) showed a positive and significant correlation with Hb and PCV in both crisis and steady states (r = 0.820, p = 0.02). Additionally, RPI and RC were significantly correlated in patients on and off hydroxyurea (p < 0.01). Only 2 (4.4%) SCA patients demonstrated appropriate bone marrow response, while the remaining 43 (95.6%) SCA patients were hypoproliferative.Conclusion: This study found derangements in the reticulocyte parameters indicating hypoproliferative anaemia. There is a need to monitor the patients closely by periodic reticulocyte counts for overall improved patient outcomes and quality of life in SCA patients.
Keywords: Sickle Cell Anaemia; hydroxyurea; reticulocyte count; reticulocyte production index; hypoproliferative anaemia; absolute reticulocyte count